2012
DOI: 10.3109/01902148.2012.721860
|View full text |Cite
|
Sign up to set email alerts
|

Potential of sivelestat in protection against severe acute pancreatitis-associated lung injury in rats

Abstract: The incidence of acute pancreatitis has been rising worldwide in the past few decades. Despite extensive research efforts, the population-based mortality from acute pancreatitis remains high. Since dysfunction of multiple vital organs, most importantly the lungs, is the major cause of early death in acute pancreatitis patients, developing effective strategies to manage lung injury has become one of the focuses of recent research efforts aiming at improving the outcome of patients with acute pancreatitis. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…A recent study showed that neutrophil-derived MMP-9 might play an important role in AP. 13 We found that challenge with taurocholate increased plasma levels of MMP-9 by nearly 8-fold ( Figure 4). Inhibition of NET formation reduced circulating levels of MMP-9 by 93% in animals exposed to taurocholate ( Figure 4).…”
Section: Net Activity Regulates Systemic Inflammationmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study showed that neutrophil-derived MMP-9 might play an important role in AP. 13 We found that challenge with taurocholate increased plasma levels of MMP-9 by nearly 8-fold ( Figure 4). Inhibition of NET formation reduced circulating levels of MMP-9 by 93% in animals exposed to taurocholate ( Figure 4).…”
Section: Net Activity Regulates Systemic Inflammationmentioning
confidence: 91%
“…It has been reported that neutrophil-derived reactive oxygen species (ROS) and enzymes, such as elastase and matrix metalloproteinase-9 (MMP-9) might contribute to neutrophil-mediated tissue damage in AP. 13,14 On top of those proposed mechanisms thus far, new aspects of neutrophil biology might help to explain how neutrophils cause tissue injury in the inflamed pancreas. Recent findings have demonstrated that activated neutrophils, beside secretion of antimicrobial compounds and phagocytic killing, can eliminate invading microorganisms by expelling nuclear DNA forming extracellular web-like structures decorated with nuclear histones as well as granular and cytoplasmic proteins.…”
Section: Introductionmentioning
confidence: 98%
“…Since this study was an extension of a previous study from our group, the animals and their allocation, as well as the methods of pancreatitis induction and sivelestat treatment, were the same as described in our previous study (9). In summary, adult male Sprague-Dawley rats were randomized into the following groups: i) the experimental acute pancreatitis (EAP) group in which rats were induced to develop acute pancreatitis by the administration of sodium taurocholate through laparotomy under anesthesia; ii) the EAP plus sivelestat treatment group in which rats were injected with 2 mg/kg sivelestat through the superficial dorsal vein of the penis immediately following EAP induction; and iii) the control group in which a sham laparotomy was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue homogenate was prepared from frozen renal specimens using the method described for the homogenate preparation of lung tissue in our previous study (9). NE activity was determined spectrophotometrically using a chromogenic substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation